Given the function defined by g(x) = 2x-5, find the following g(-3)

The answer is -11.

Expert answered|ArslanBasit|Points 1925|

Question

Asked 2/23/2013 11:19:15 AM

Updated 357 days ago|7/29/2023 12:37:54 AM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

3

To find g(-3), substitute -3 for x in the function g(x):

g(-3) = 2(-3) - 5

Now, perform the calculations:

g(-3) = -6 - 5

g(-3) = -11

So, g(-3) is equal to -11.

g(-3) = 2(-3) - 5

Now, perform the calculations:

g(-3) = -6 - 5

g(-3) = -11

So, g(-3) is equal to -11.

Added 357 days ago|7/29/2023 12:37:54 AM

This answer has been confirmed as correct and helpful.

39,304,382

questions answered

There are no comments.